Context-aware cluster-based hierarchical protocol for Wireless Sensor Networks. (24th September 2009) - Haque, Md Enamul; Matsumoto, Noriko; Yoshida, Norihiko
Wireless Sensor Network (WSN) has been a key research topic for its multi dimensional applications. Its applications require accurate information collecting as well as, longer service life. In WSN, employing an efficient routing protocol plays a significant role in attaining such service requirements. In this paper, an energy efficient routing protocol, Context-Aware Clustering Hierarchy (CACH) has been proposed where cluster formation is entirely based on the context of the environment. Moreover, an efficient technique has been utilised to avoid similar data traffic across the network and cluster head role has been equally distributed among the nodes. The performance in the simulation shows substantial amount of energy optimisation.